Chili Pepper Cultivation Using Several Spacings Intercropped with Immature Oil Palm - Hegar Nurjannah; Lucy Robiartini; Susilawati Susilawati (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2021)
Oil palm (Elaeis guineensis Jacq.) belong to the Arecaceae family, is economically valuable for oil production. The objective of this study was to evaluate the growth of immature oil palm intercropped with red chili pepper and to evaluate the best spacing for red chilli cultivation between immature oil palm. The study was conducted in Rimba Jaya Village, Air Kumbang District, Banyuasin Regency, South Sumatra. The study began in October 2017 until February 2018. The design used for the red chili pepper cultivation was a one-factor Randomized Block Design. Spacing used as treatments, namely: (M1 = 50 x 50 cm ; M2 = 60 x 60 cm ; M3 = 70 x 70 cm). Treatments were placed in 5 groups. The results showed that plant height, stem diameter, canopy diameter and the greenness level of palm oil leaves did not affect by the presence of red chili pepper. While spacing of 50 x 50 cm provided a positive response to the growth and yield of chili pepper. The highest yield of red chili was 10.41 kg produced in 50 x 50 cm spacing.